THE INFLUENCE OF THE MARKETING MIX ON THE EXPORT SALES VOLUMES OF TEXTILE PRODUCT AT PT. PRIMATEXCO INDONESIA - Hani Khairunisa; Budi Prasetya; Nur Rini (Politeknik Negeri Semarang, 2015)
This study entitled “The Influence of The Marketing Mix on The Export Sales Volumes of TextileProduct at PT. Primatexco Indonesia”, aimed to analyze the influence of the marketing mix onthe export sales volumes. This study used secondary data taken from PT. Primatexco Indonesia,per month in 2004 through 2014.The analysis method that is used in this research is using normality test, classical assumptiontest (which includes heteroscedasticity, multicollinearity, autocorrelation), multiple linearregression analysis, T-test, F-test, and R2(coefficient of determination).Based on the simultaneous test, the results proved that independent variables that is product, place, promotion, and price simultaneously had a significant influence on the export salesvolumes with the calculated value of F values = 167.475 and sig = 0,000 < 5% this meansindependent variables product, place, promotion, and price simultaneously significant influenceon the dependent variable (export sales volume). In other words, the independent variables areable to explain the amount of the dependent variable.Based on partial analysis, the results proved that the three independent variables that is product,place, and price significantly influenced on the export sales volumes. On product variable tcount value of 13.887 was > t table 2.29 which means that Ho was rejected and Ha wasaccepted. While the promotion variable did not have any influence significantly on the exportsales volumes, because t count value -1.609 was < t table, so Ho was accepted and Ha wasrejected.The results of multiple linear regression test shows that all independents variables that isproduct, place, and price had a positive influence on the export sales. The greatest positiveinfluence on export sales volumes was product variable (X1), it is shown from the regressioncoefficient of 8.976, followed by price variable (X4) with a regression coefficient of 1.451E-5,followed by place variable (X2) with a regression coefficient of 2.383E-6. While the promotionvariable (X3) with coefficient regression of -6.210E-10, it means that promotion variable doesnot have any positive influence on the export sales volumes.Keywords: Product, Place, Promotion, Price, Export Sales Volumes, Textile Products